1994
DOI: 10.1088/0031-8949/50/4/019
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of the schottky boundary condition for numerical simulation of Schottky and MESFET structure

Abstract: A critical analysis of the existing boundary conditions at the Schottky contact is described. It is supported by the results of simulation and comparison with experimental observations. 1-V measurements on the CrSi,-Si Schottky structure were carried out to investigate the contribution of tunneling current to the total current. It is found that at room temperature this effect can be neglected. Boundary conditions based on a revised current flow theory through the Schottky junction seems to be the best choice f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Thus, we begin our analysis by briefly demonstrating that our methodology can capture the majority and minority carrier electrostatics of MS junctions, by numerically solving the complete drift–diffusion equations utilizing the boundary conditions derived in section . The primary goal of this analysis is to verify that the implementation procedure discussed in our present work can capture the electrostatics and carrier transport of an MS Schottky junctionwhich has been well explored in the device physics literature. , Particular attention will be given to modeling the transport of minority carriers due to its importance in photocatalytic semiconductor–liquid junctions, which is the ultimate goal of our present work.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Thus, we begin our analysis by briefly demonstrating that our methodology can capture the majority and minority carrier electrostatics of MS junctions, by numerically solving the complete drift–diffusion equations utilizing the boundary conditions derived in section . The primary goal of this analysis is to verify that the implementation procedure discussed in our present work can capture the electrostatics and carrier transport of an MS Schottky junctionwhich has been well explored in the device physics literature. , Particular attention will be given to modeling the transport of minority carriers due to its importance in photocatalytic semiconductor–liquid junctions, which is the ultimate goal of our present work.…”
Section: Resultsmentioning
confidence: 86%
“…Thus, we have demonstrated that our approach captures the necessary minority carrier physics, an important prelude to evaluating SL pseudo-Schottky contacts which are dominated by minority carrier transport. Finally, the calculated current density (as shown in Figure e) exhibits the rectifying character of a typical Schottky contact and can be compared with numerous current–voltage characteristics present in the device physics literature. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations